Spillovers And Governance: An Analysis Of Knowledge And Reputational Spillovers In Information Technology - Mayer, Kyle J. (Academy of Management Journal, 2006)
Investigating spillovers (potential costs and benefits to a firm that extend beyond an individual transaction), I integrate transaction cost theory and the knowledge-based view of the firm in an effort to better understand the efficient governance of knowledge. Contracts with detailed task descriptions were associated with transactions with the potential to generate new and reusable knowledge. The risk of a firm's technology spilling over to others and the risk of reputation-impairing spillovers were associated with suppliers using their own employees rather than subcontractors. Thus, results suggest that the creation and protection of knowledge are key factors in understanding governance decisions.